728 Antibiotics and response to immunotherapy: real-world experience. (10th December 2020) - Ahmed, Yasar; Calvert, Paula
Abstract : Background: Immune checkpoint inhibitors (ICI) have altered the therapeutic paradigm of advanced non-small cell lung cancer (NSCLC) and have become an attractive treatment strategy in several malignancies. The identification of reliable predictors associated with resistance is essential to dictate new approaches to broaden responder groups.Growing evidence has shown that the gut microbiome is an important regulator of the systemic immune system and is involved in the response to ICI. The aim of the study was to evaluate the association between antibiotics use & ICI efficacy in advanced NSCLC Methods: A retrospective, single-centre study of unselected patients with advanced NSCLC treated with ICI between June 2016 to May 2019. We included consecutive patients who received at least one dose of PD-1 inhibitors (Nivolumab or pembrolizumab) Clinicopathologic characteristics and the status of any oral or intravenous antibiotic use were evaluated. Antibiotic use was defined as antibiotic treatment at any time between 4-weeks pre- and 4-weeks post the start of ICI (table 1 ).Progression-Free Survival (PFS) & Overall Survival (OS) were estimated with Kaplan-Meier method & compared between Abx groups. Cox proportional model was used for multivariate analyses Results: After a median follow-up of 8.5 months [0.3–56.4], a significant improvement in PFS was observed in untreated group compared to Antibiotics treated group. 12.4 months (95%CI, 1.9–22.9) vs 4.1 months (95%CI, 2.6–5.6) (p < 0.001; figure 1 ). Similarly, OS among patients with no Antibiotics usage was significantly higher: 28.2 months (95%CI, not calculated) vs 12.5 months (95%CI, 10.8–14.2) (p < 0.001; figure 2 ). Conclusions: Our results point to a detrimental effect of antibiotics on treatment outcome to ICI therapy.The antibiotics use was significantly associated with attenuated efficacy of anti-PD-1 therapies in patients with NSCLC Modulation of antibiotic-related changes of gut microbiota may be important to improve clinical outcomes in ICI for cancer treatmentIn patients needing antibiotics, careful selection to avoid antimicrobial agents that modulate immune responses should also be taken into considerationFurther studies are needed to determine the regimen, length of antibiotics treatment and its relation to survival benefits References: Wilson, Brooke E., et al. 'The effect of antibiotics on clinical outcomes in immune-checkpoint blockade: a systematic review and meta-analysis of observational studies.' Cancer Immunology, Immunotherapy 2019:1–12. Elkrief, A., et al. 'The negative impact of antibiotics on outcomes in cancer patients treated with immunotherapy: a new independent prognostic factor?. ' Annals of Oncology 2019;30(10): 1572–1579. Villéger, Romain, et al. 'Intestinal microbiota: a novel target to improve anti-tumor treatment?.' International Journal of Molecular Sciences 2019;20(18):4584